Reshaping the Quinquennial Plan for Indigenous Peoples: Dialoguing with a Gnöbe Community Leader - Kevin Armando Brand Fonseca; Christian Fallas Escobar (Revista de Lenguas Modernas, 2019)
In this paper, we engaged in dialogue with a Gnöbe community leader, who was also a teacher of English, so to analyze how the Quinquennial Plan for Indigenous Peoples in Costa Rica (QPIP) caters to the needs and goals of the indigenous students enrolled in the Bachelor’s in English Teaching at Universidad Nacional, Coto Campus. The efforts made by the university authorities and the associate faculty during the implementation of the QPIP had previously been scrutinized—unraveling that the objectives of the plan have partially been met and that more courses of action are required to ensure successful outcomes (Fallas & Brand, forthcoming). By examining the interview conducted with the participant of the study, based on tenets of the Narrative Approach, we shed light on the hardships faced by Gnöbe students in the education system, the circulating discourses held by First Nation Communities regarding education and bilingualism, and the solutions proposed by the community stakeholder to alleviate the problems encountered by QPIP students in their college life. We finish this paper by translating the leader’s voice into applicable suggestions that may help professors of the English Department and the administration of the university retain indigenous students by promoting more culturally relevant pedagogies geared to their academic success and development of their cultural identity and affiliation.